1.7k views
4 votes
Simplify each expression.

Simplify each expression.-example-1
User Gout
by
5.2k points

1 Answer

3 votes
1)B -26-27x
steps :distribute ,-9 times 3 =-27 , -9 times 3x = -27x , now combine like terms :you have a 1 and a -27 ,1-27=-26,and you left with -27



2)D 11-49x
steps :distribute , positive 7 times 1= 7 and then positive 7 times negative 7x =-49, now combine like terms ,since you have a positive 4 combine it with positive 7 which is 11 and finally put it together with -49x which it would look like 11-49x
User Dave Long
by
6.2k points